2015
DOI: 10.1021/acs.inorgchem.5b01766
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Fluorescence Response of PET Sensors via the Metal-Ion π-Contacting Ability of the Fluorophore: Coumarin, a Weaker π Contacter

Abstract: The π-contact hypothesis, that quenching of the fluorescence of complexes of photoinduced electron transfer sensors with heavy diamagnetic metal ions may be caused by π contacts between the metal ion and the fluorophore of the sensor, is examined with a study of the fluorescent properties of the sensor 4-[[bis(2-pyridinylmethyl)amino]methyl]-6,7-dimethoxy-1-benzopyran-2-one (cdpa) and the structures of its complexes with some metal ions. The coumarin-type fluorophore of cdpa is a weaker π-contact former than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The order of ability to induce a CHEF effect with the 289 nm peak in Figure is what one would expect if the fluorescence of the DB‐cyclen ligand and its metal ion complexes was due to the fluorescing non π contacted benzyl groups projecting out into the surrounding solution, with little influence from the cyclen moiety or any complexed metal ions it might contain. Zn II shows negligible ability to form π contacts, so that one would expect the fluorescence at 289 nm to be simply that of any non‐π contacted benzyl groups: these peaks are also observed for the Cd II , Hg II , and Cu II complexes at 289 nm, although these are much less intense, presumably due to π contact formation in solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The order of ability to induce a CHEF effect with the 289 nm peak in Figure is what one would expect if the fluorescence of the DB‐cyclen ligand and its metal ion complexes was due to the fluorescing non π contacted benzyl groups projecting out into the surrounding solution, with little influence from the cyclen moiety or any complexed metal ions it might contain. Zn II shows negligible ability to form π contacts, so that one would expect the fluorescence at 289 nm to be simply that of any non‐π contacted benzyl groups: these peaks are also observed for the Cd II , Hg II , and Cu II complexes at 289 nm, although these are much less intense, presumably due to π contact formation in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The idea that the increase in fluorescence intensity was caused by weakening of fluorescence‐quenching Cd ··· C π contacts was supported by structural studies that showed that the Cd ··· C π contacts present in the Cd II adpa complex were greatly lengthened on coordination of the Cl – , Br – , SCN – , and S 2 O 3 2– as compared to the less covalently binding NO 3 – anion, or, as predicted by DFT calculation, coordinated water molecules . The more weakly π contacting coumarin fluorophore of cdpa yields Cd II complexes that do not respond with increases in fluorescence intensity on coordination of anions, since no π contacts are present to be disrupted . The suggestion that fluorescence in adpa complexes was quenched by formation of π contacts was supported by DFT calculations …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The fluorescence and absorbance decreased upon addition of more than 55 µM and 45 µM Cu 2+ respectively, that might be respected to the paramagnetic nature of Cu 2+ [27,36,37]. Paramagnetic square-planar or tetragonally distorted metal ions such as Co 2+ , Cr 3+ , Cu 2+ , Fe 3+ , Ni 2+ , and Pd 2+ are able to quench the fluorescence of optical chemosensors which is presumptively undesirable for analytical purposes [38]. The paramagnetic effect is basically the result of an enhanced electronic states' mixing (considered as a formally forbidden intersystem crossing) of a ligand by means of the inhomogeneous magnetic field of the paramagnetic ion [39].…”
Section: Optical Sensing Propertiesmentioning
confidence: 99%